The role of accounting responsibility in the success of the reform of financial and administrative / applied research in high School - حسن حنان عبد الله (Journal of Economics and Administrative Sciences, 2017)
The reform process is a dynamic process going on, especially the administrative and financial reform, which contributes to the work and directing operations towards success and continuous development, which requires determining the validity and the responsibility and the rights and duties of all officials in the school settings (within the formations educational institutions) for the purpose of reducing the administrative and financial corruption, and then ensure management efficient and effective way by taking advantage of the physical, financial and human resources available to achieve the greatest benefit at the lowest cost to the fact that the follow-up performance on an ongoing basis in accordance with the specific of powers and responsibilities to help in the success of the administrative reform of the financial, including guarantee better performance and raising its efficiency levels, by specifying the duties and powers according to the administrative legal formula and according to scientific qualifications process promotes a sense of responsibility when tasks, especially, commitment to the principle of completion (the administrative and financial reform is everyone’s responsibility and goal for all), and accordingly have been identified problem of the research included the lack of educational foundation them (schools) to a regular mechanism for the distribution of authorities and responsibilities clear who is welcome her on positions of responsibility within the organizational structure to it, which negatively affects the reduction of administrative and financial corruption and the difficulty repaired later. And research aims to adopt the approach just for the distribution of powers and responsibilities for anyone who is worthy her clearly on the responsibility centers to reduce corruption and facilitate the task of reform later .so that conclusion that the success of the reform of administrative and financial Transaction affected by choosing the right person to manage the responsibility which is determined by the authorities and responsibilities centers. Accordingly, the researcher recommended following the approach properly represented accounting responsibility (when the distribution of powers and responsibilities of who is welcome her at the division of the organizational structure to the responsibility centers) to ensure the success of the reform process for the application of hypothesis that the success of the reform of administrative and financial is when the division’s organizational structure clearly and precisely to the responsibility centers are distributed in responsibilities and powers of their qualified using financial, material and human resources available makes it easy to keep track of the completion of tasks (to perform), to identify the weaknesses (corruption) and fix& reform it the right time and to avoid the occurrence later.